ANALISIS EFISIENSI DAN EFEKTIVITAS PENGELOLAANKEUANGAN KABUPATEN SIDOARJO TAHUN 2022,2023 DAN 2024 - Grace Victress Gabriel Belen; Ria Ekanindya Widyaningsih (NETIZEN: JOURNAL OF SOCIETY AND BUSSINESS, 2025)
This study aims to analyze the eficiency and efectiveness of financial management in the Sidoarjo Regency Government during the fiscal years 2022, 2023, and 2024. A descriptive quantitative approach was employed by calculating eficiency and efectiveness ratios based on budget realization reports. The results show that the level offinancial eficiencyfluctuated: it was classified as highly ineficient in 2022 (107.66%),fairly eficient in 2023 (83.88%), and less  eficient  in  2024  (98.46%).  Meanwhile,   the  level  of  efectiveness  showed  positive performance,  with  very  efective  outcomes  in  2022  (101.18%)  and  2024  (104. 77%),  and moderately  efective  results  in  2023  (81.07%).  These findings  indicate  improvements  in financial governance in terms of eficiency and stability in achieving regional revenue targets. The results are in line with the theory of eficiency by Mahmudi (2016), which emphasizes the optimal use of resources  to produce  maximum  output, and the  theory  of efectiveness  by Mardiasmo (2009), which highlights the achievement of planned objectives. Therefore, the financial management of Sidoarjo Regency is considered to be improving and increasingly aligned with the  principles of good governance in public financial management.